Iniciativas de integração e consolidação de bolsas: a experiência européia e norte-americana e os efeitos na América Latina - Pamboukdjian, Lucy (2006)
This paper analyses the features that led the stock exchanges in Latin America to promote the integration initiatives that are currently in progress. The evaluation takes the experiences in integration and consolidation observed in Europe and the United States as main reference, as well as the opening of capital markets, introduction of electronic trading systems and demutualization processes, along with the increasing participation of institutional investors as main drivers of the transformation seen in the recent years. Since the late 1980 s, the capital markets worldwide have seen the modernization of the stock and derivatives exchanges. This movement has been occurring simultaneously to the opening of the capital markets and to the flows of capital led by institutional investors, which seem to have stimulated the adoption of more efficient electronic trading systems for the securities trading. In this sense, stock exchanges and market intermediaries started using technology to strengthen the efficiency of its intermediation models, as well as to broaden access with smaller trading costs to investors. In order to achieve more flexibility and raise financial resources to conduct these changes, the demutualization process has emerged allowing exchanges to become for-profit and market driven companies, which segregated the trading rights and the ownership rights of the intermediaries in the exchanges